Performance Evaluation of Oil Palm Trunk Starch as Binder, Modified by Sodium Trimetaphosphate - Mohd Zulhairie, Razali; Junidah, Lamaming; Othman, Sulaiman; Rokiah, Hashim; Mohammed, Nasir; Mohd Ezwan, Selamat; Nadiah, Jumhuri; Salim, Hiziroglu (RMP Publications, 2022)
The objective of this study was to evaluate the properties of particleboard prepared from starch-based adhesive, modified with sodium trimetaphosphate as a binder. Three-layer experimental panels were manufactured from a homogenous mixture of Acacia mangium and rubberwood. Panels were prepared from two different target densities of 0.60 g/cm3 and 0.80 g/cm3 and four different combinations of adhesive. The four combinations of adhesives were sequentially urea-formaldehyde (UF), native oil palm trunk starch (OPT-starch), sodium trimetaphosphate (STMP), modified starch, and STMP-starch mixed with 2% UF. Adhesive properties were analyzed by thermogravimetric (TGA), differential calorimetry (DSC), X-ray diffractometer (XRD), and scanning electron microscopy (SEM). The prepared panels were evaluated for their physical and mechanical properties. An experimental panel with 0.80 g/cm3 density showed better mechanical and physical properties compared to 0.60 g/cm3 . Oil palm trunk starch modified with sodium trimetaphosphate exhibited an improvement in physical and mechanical properties when it was used in combination with UF resin.